SOSIALISASI ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK (AUPB) BAGI PERANGKAT PEMERINTAH DAERAH DALAM PELAYANAN PUBLIK DI KANTOR DESA BALERAJA, GANTAR, INDRAMAYU - Rahim, Abdur; Darussalam, Muhammad Illyas; Suparmin, Suparmin; Fitria, Dina; zafira, Rufaidah; Antasya, Faridah; Nugroho, Agung; Nahdah, Athaya Nisrina; Suhady, Suhady; Khalida, Rizqiana; Ridho, Fakhru; Abdillah, Muhammad Mukhlis (LPPM Universitas Bina Bangsa, 2025)
Good governance is the fundamental foundation for establishing effective management, particularly at the village level. The General Principles of Good Governance (AUPB) serve as essential guidelines that must be implemented in government administration to ensure transparent, accountable, and responsive public services. However, challenges remain in the implementation of AUPB by village officials due to a lack of understanding and limited resources. This community service initiative aims to socialize AUPB among village officials at the Baleraja Village Office, Gantar, Indramayu. The methods employed include seminars, interactive discussions, AUPB-based public service simulations, and evaluations through pre-tests and post-tests. The results of this initiative indicate an improvement in village officials’ understanding of AUPB, as well as heightened awareness of the importance of transparency and accountability in public services. With the optimal implementation of AUPB, the quality of public services in villages is expected to improve, thereby strengthening public trust in village governance.